Pengembangan dan Komersialisasi Desain Produk Aksesoris Interior Berbahan Baku Kain Perca Sebagai Upaya Meningkatkan Komersialisasi Usaha Bank Sampah Gulon Asri - Rohadatul 'Aisy, Nadhifia Iryadini; Alimin, Nurhayatu Nufut; Putri Novitabella, Trisna Dwi; Pradini Priliana, Silmi Cahya; Safi’i, Wisnu imam; Pramesti, Sharfina Djati (Adi Widya : Jurnal Pengabdian Masyarakat, 2025)
The service activity is a continuation of the previous service activity, which is almost entering the final stage of efforts to commercialize Gulon Asri waste bank products. This service activity consists of material delivery activities and product making workshop activities along with recording video tutorials of the products being worked on. At this stage, waste bank women are taught to make video tutorials which can be used as a means of education about recycling fabric waste as well as a promotional medium for the products produced by the waste bank.